Prediction of the optimum aqueous phase composition of a triglyceride microemulsion using response surface methodology - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (Elsevier, 2013)
This paper presents the application of response surface methodology to predict the optimum aqueous phase composition of a triglyceride microemulsion for enhanced oil recovery. The two models capturing the relationships between interfacial tension and tertiary oil recovery data with the aqueous phase composition were validated prior to optimization. It was predicted that the optimum aqueous phase contains 3 wt% sodium chloride, 0.98 wt% alkyl polyglycosides, and 2.98 wt% glyceryl monooleate. At this composition the corresponding interfacial tension is minimum (0.000229451 mN/m) and the tertiary oil recovery is maximum (71.7865%). The predicted optimum aqueous phase composition using historical-data design is close to the experimental value.